An In Vitro Model for Assessing Corneal Keratocyte Spreading and Migration on Aligned Fibrillar Collagen - Pouriska B. Kivanany; Kyle C. Grose; Nihan Yonet-Tanyeri; Sujal Manohar; Yukta Sunkara; Kevin H. Lam; David W. Schmidtke; Victor D. Varner; W. Matthew Petroll (Journal of Functional Biomaterials, 2018)
Background: Corneal stromal cells (keratocytes) are responsible for developing and maintaining normal corneal structure and transparency, and for repairing the tissue after injury. Corneal keratocytes reside between highly aligned collagen lamellae in vivo. In addition to growth factors and other soluble biochemical factors, feedback from the extracellular matrix (ECM) itself has been shown to modulate corneal keratocyte behavior. Methods: In this study, we fabricate aligned collagen substrates using a microfluidics approach and assess their impact on corneal keratocyte morphology, cytoskeletal organization, and patterning after stimulation with platelet derived growth factor (PDGF) or transforming growth factor beta 1 (TGFβ). We also use time-lapse imaging to visualize the dynamic interactions between cells and fibrillar collagen during wound repopulation following an in vitro freeze injury. Results: Significant co-alignment between keratocytes and aligned collagen fibrils was detected, and the degree of cell/ECM co-alignment further increased in the presence of PDGF or TGFβ. Freeze injury produced an area of cell death without disrupting the collagen. High magnification, time-lapse differential interference contrast (DIC) imaging allowed cell movement and subcellular interactions with the underlying collagen fibrils to be directly visualized. Conclusions: With continued development, this experimental model could be an important tool for accessing how the integration of multiple biophysical and biochemical signals regulate corneal keratocyte differentiation.